Progesterone-Releasing Vaginal Ring for Luteal Phase Support After Superovulation and Intrauterine Insemination Cycles, a Pilot Study [Anel Vaginal de Progesterona Para O Suporte Lúteo Após Super-Ovulação Em Ciclos de Inseminação Intrauterina: Estudo Piloto] - Schwarze-Meza, J (Sociedade Brasileira de Reproducao Assistida, 2013)
Objective: The main objective of this pilot study was to determine whether a progesterone-releasing vaginal ring is a good alternative for luteal phase support for patients undergoing intrauterine insemination after ovulation induction with sc gonadotrophins. Material and methods: We performed a multi-center study involving three different reproductive medicine units. Patients included were diagnosed with unexplained infertility and this was their first IUI cycle after ovulation induction with rFSH (Puregon ®) and ovulation induction with urinary HCG (Pregnyl ®). The day of insemination patients were randomized to receive luteal phase supplementation with progesterone vaginal ring (Fertiring ®) or no supplementation. Results: One hundred patients were invited to participate, and completed the study. Forty seven received luteal phase support with Fertiring ®. Overall the pregnancy rate was 15%. It was higher, although without reaching statistical significance, in the group receiving luteal phase support Fertirng ® (19.1%) than in the group without supplementation(11.3%). Conclusions: In this study, patients undergoing ovulation induction with Puregon ® and received luteal phase support with Fertiring ® showed a higher pregnancy rate than those who received no luteal phase support, although statistical significance was not achieved.